The Radical Left after 1968: From Ideological Craze to Reconfiguration of Politics. (10th November 2017) - Falciola, Luca
Abstract : By the mid-1970s, Jerry Rubin—icon of American radicalism and cofounder of the Yippies, who campaigned in 1968 to elect a pig as president of the United States and appeared before the House Un-American Activities Committee dressed in an eighteenth-century Revolutionary War uniform—had transformed himself from protester to successful businessman. He launched a new career on Wall Street as a stockbroker, became known for his promotion of "networking, " bringing together yuppies at parties in Manhattan, and was an early investor in Apple Computer. For a long time, both in public memory and in many historical accounts, Rubin's conversion embodied the path of an entire generation of leftists who hastily shifted from the ideological craze of 1968–1970 to the disillusionment of the so-called "me decade."